A responsabilidade social como forma de criação de valor nas organizações do PSI-20 da Euronext Lisboa - Santos, Daniela Botelho Cardoso Ramos dos (2021)
Promoting and implementing Corporate Social Responsibility (CSR) should be seen as a way for organizations to create a competitive advantage since its stakeholders are increasingly concerned and aware of environmental and social issues. Thus, reporting sustainability on a voluntary basis is not only a means of disclosing the positive and negative impacts that organizations have on society, but also a key element in their transparency. This research aims to analyze the relationship between CSR performance variables and the economic performance of organizations listed in the PSI-20 of Euronext Lisbon in order to understand whether the adoption of CSR measures, as well as their disclosure, can create value and benefits for them. To this end, based on a qualitative and quantitative research methodology, we read the Sustainability Reports and the Annual Reports and Accounts, published by the companies in the period from 2017 to 2019, in order to determine the percentages of response to environmental and social performance indicators. Then, in order to assess the relationship between social responsibility and economic and financial performance, the financial statements were analyzed taking into account the following economic and financial indicators: ROA, Return on Sales Ratio, ROE and Debt Ratio. The results obtained show that there is an increase in the disclosure of environmental and social information over the three years and, therefore, it is clear that CSR can only be justified as long as it adds business value. However, the results on the analysis between CSR performance and economic-financial performance were not conclusive and evident.